2021
DOI: 10.1186/s12935-021-02214-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum GGT/ALT ratio predicts vascular invasion in HBV-related HCC

Abstract: Background The gamma-glutamyl transferase (GGT) to alanine aminotransferase (ALT) ratio has been reported as an effective predictor of the severity of hepatitis and HCC. The purpose of this study was to determine the role of the GGT/ALT ratio in the prediction of vascular invasion and survival outcomes in patients with hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). Methods The risk factors for vascular invasion were determined by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Gamma-glutamyltransferase (GGT), as a cell surface enzyme, has been proven to be a marker of many cancers ( 29 31 ). Tumor invasion and the release of inflammatory factors often lead to the destruction of hepatocytes, which is characterized by increased GGT in the peripheral blood ( 32 , 33 ). It has been reported that GGT is a reliable marker of oxidative stress, and the increased expression of GGT in tumor cells is associated with the production of ROS, which can promote the invasion and migration of tumor cells ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gamma-glutamyltransferase (GGT), as a cell surface enzyme, has been proven to be a marker of many cancers ( 29 31 ). Tumor invasion and the release of inflammatory factors often lead to the destruction of hepatocytes, which is characterized by increased GGT in the peripheral blood ( 32 , 33 ). It has been reported that GGT is a reliable marker of oxidative stress, and the increased expression of GGT in tumor cells is associated with the production of ROS, which can promote the invasion and migration of tumor cells ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular invasion is a significant but poor prognostic factor of survival in patients with HCC ( 45 ), Luo et al. disclosed that a high GGT/ALT ratio was identified as an independent risk factor for vascular invasion in patients with HCC ( 46 ). Additionally, Ju et al.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al reported that hepatitis B patients with a higher GGT/ALT ratio were more likely to develop liver cancer (44). Vascular invasion is a significant but poor prognostic factor of survival in patients with HCC (45), Luo et al disclosed that a high GGT/ALT ratio was identified as an independent risk factor for vascular invasion in patients with HCC (46). Additionally, Ju et al observed that a higher GGT/ ALT ratio correlated with a more severe tumor burden in patients with HBV-related HCC, including tumor size, tumor capsule, and shortened survival time (18).…”
Section: Discussionmentioning
confidence: 99%
“…Our experimental data disclosed a negative correlation between RAB11B expression and pathology grade, T-Bil, GGT, and PD-L1. T-Bil and GGT are both important indicators of liver function in patients and are combined with other objective parameters in clinical diagnosis, such as ALBI score, which is considered a gold standard for the diagnosis of HCC patients [ 43 , 44 ]. Abnormally upregulated T-Bil or GGT is often associated with the occurrence of hepatitis, obstructive jaundice, or cirrhosis.…”
Section: Discussionmentioning
confidence: 99%